A Field Research Study Which Analyses Ethnic Values and Aesthetic Art Education: As Observed in Wisconsin Indian Community Schools - Stuhr, Patricia L. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1986)
To investigate allegations by Indian artists that their ethnic values/traditions are being omitted from art curricula in their Wisconsin community schools, the study conducted ethnographic observations and interviews in a reservation elementary public school, a public elementary and high school located just outside the reservation, and a reservation elementary tribal school contracted by the Bureau of Indian Affairs (BIA). The research examined school and classroom environment, teacher theory, teacher practice, and student art activities and learning. Results showed that only the BIA school considered the aesthetic/art heritage and ethnic values of its students. Factors determining whether students' heritage/values were considered were teacher's ethnic background, university courses in preparation for teaching art, and exposure to cultural values, art forms, and history of Indian ethnic groups. The study recommends that to utilize art as a tool to dissolve bigotry between Indians and whites in Wisconsin, more Indian art teachers should be hired by Indian communities; white teachers' education should include Indian values systems, traditions, and art forms; Indian artists should be utilized in schools; Indian students should be encouraged to express their culture through their art production; and teachers should design projects to allow for such expression. (NEC)
ERIC Note: Paper presented at the American Educational Research Association (67th, San Francisco, CA, April 16-20, 1986).
Educational level discussed: Elementary Secondary Education.
Researchers.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Aesthetic Education; American Indian Culture; American Indian Education; Art Education; Art Teachers; Course Content; Cultural Education; Cultural Enrichment; Curriculum; Elementary Secondary Education; Ethnic Studies; Nonreservation American Indians; Relevance (Education); Reservation American Indians; Teacher Education Curriculum; Teacher Qualifications; Wisconsin; Speeches/Meeting Papers; Reports, Research